Análise da origem das manifestações patológicas em pavimento de concreto de uma rodovia pelo método dos elementos finitos: estudo de caso - Bolina, F.; Tutikian, B. (Revista ALCONPAT, 2014)
Regarding issues pertaining to infrastructure, it is observed that the Brazilian’s highway Mário Quintana, call ERS-118, located in the state of Rio Grande do Sul , Brazil , announces in alarming conservations circumstances and trafficability due to the high deterioration degree of the pavement . The objective of this work is to analyze the possible causes that produced the pathological manifestations in the pavement concrete. The study was based on the structural analysis of these elements. Therefore, this study was based on the method of finite elements and subsequent analysis of the results produced by the correlation between stress versus number of permissible axle bushings. The study was divided into three parts: (1) method of pavement’s structural analysis, (2) discussion of the results and (3) conclusion. As a result, it was found that many of the pathological manifestations may have stemmed from the thermal effects arising in the pavement concrete. Keywords: Pathology. Pavements. Concrete